2012
DOI: 10.1104/pp.112.200659
|View full text |Cite
|
Sign up to set email alerts
|

The CopRS Two-Component System Is Responsible for Resistance to Copper in the Cyanobacterium Synechocystis sp. PCC 6803      

Abstract: Photosynthetic organisms need copper for cytochrome oxidase and for plastocyanin in the fundamental processes of respiration and photosynthesis. However, excess of free copper is detrimental inside the cells and therefore organisms have developed homeostatic mechanisms to tightly regulate its acquisition, sequestration, and efflux. Herein we show that the CopRS two-component system (also known as Hik31-Rre34) is essential for copper resistance in Synechocystis sp. PCC 6803. It regulates expression of a putativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
125
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(137 citation statements)
references
References 63 publications
(90 reference statements)
12
125
0
Order By: Relevance
“…The induction of expression of this operon was likely due to degradation of the electron carrier plastocyanin and subsequent release of bound copper. A similar upregulation was previously observed upon addition of DBMIB (2,5-dibromo-3-methyl-6-isopropyl-p- benzoquinone), which blocks electron transfer to PC and oxidizes the PC pool (47).…”
Section: Resultssupporting
confidence: 52%
“…The induction of expression of this operon was likely due to degradation of the electron carrier plastocyanin and subsequent release of bound copper. A similar upregulation was previously observed upon addition of DBMIB (2,5-dibromo-3-methyl-6-isopropyl-p- benzoquinone), which blocks electron transfer to PC and oxidizes the PC pool (47).…”
Section: Resultssupporting
confidence: 52%
“…PCC 6803, CopRS two-component system is known to be essential for copper resistance [42]. CopS was shown to have a high affinity to bind Cu in vitro , moreover its localization both in the plasma and thylakoid membrane suggested that CopS can possibly bind and respond to Cu both in the periplamic and thylakoid lumen in Synechocystis [42]. However, further studies are warranted to completely understand the mechanism and conditions involved in Cu binding to CopS under natural conditions.…”
Section: Copper Homeostasismentioning
confidence: 99%
“…The isolated periplasmic domain of the sensor kinase CopS binds Cu 2+ but not Zn 2+ , Ni 2+ or Co 2+ , suggesting that CopS specifically responds to copper (Giner-Lamia et al, 2012). Direct repeat sequences (TTTCAT-N 5 -TTTCAT) upstream of the copBAC and copMRS transcription start sites are thought to act as binding sites of the response regulator CopR.…”
Section: Synechocystis Sp Pcc 6803mentioning
confidence: 99%
“…The unicellular cyanobacterium Synechocystis 6803 synthesizes a plasmid-borne RND-type copper efflux system encoded by the copBAC operon to cope with excess copper (Giner-Lamia et al, 2012). Either of two genetically distinct two-component CopRS systems (encoded by the chromosomal copMRS and the episomal pcopMRS operons) is sufficient to induce copBAC expression.…”
Section: Synechocystis Sp Pcc 6803mentioning
confidence: 99%